2009
DOI: 10.1111/j.1439-0264.2008.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Lung Maturation of Foetus of Diabetic Mother Rats Develop with a Diminish, but Without Changes in the Proportion of Type I and II Pneumocytes, and Decreased Expression of Protein D‐Associated Surfactant Factor

Abstract: Newborn children of diabetic mothers have an increased morbidity and mortality because of respiratory distress syndrome. We study lung histogenesis during intrauterine development of offspring of diabetic Sprague-Dawley rats at 18, 19 and 21 days of gestation (DG). Pregnant rats were grouped into diabetic (streptozotocin-induced), citrate, and control groups; five female and five male offspring were selected randomly from each group at 18, 19 and 21 DG, and a biopsy of the lung was taken and processed in paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Glycogen is processed to produce the glycerol backbone for phospholipids. Previously, links between glucose metabolism and respiratory distress were indicated by an increased incidence of respiratory distress syndrome in infants of diabetic mothers (39,40). Furthermore, glucose infusion experiments with fetal lamb lungs showed a decrease of pulmonary disaturated phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 96%
“…Glycogen is processed to produce the glycerol backbone for phospholipids. Previously, links between glucose metabolism and respiratory distress were indicated by an increased incidence of respiratory distress syndrome in infants of diabetic mothers (39,40). Furthermore, glucose infusion experiments with fetal lamb lungs showed a decrease of pulmonary disaturated phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 96%
“…The lung is an organ affected during fetal development in maternal diabetes. Several reports have addressed maternal diabetes-induced morphological and maturation alterations in the fetal lung at term, related to impairments evident both in the perinatal period and in later life of the newborn (Koskinen et al, 2011;Milla and Zirbes, 2012;Trevino-Alanis et al, 2009;Vela-Huerta et al, 2007).…”
Section: Tablementioning
confidence: 98%
“…In human and rodent fetuses, the lung is an organ clearly affected by maternal diabetes, in which structural, physiological and maturation defects are related to increased risks of respiratory distress syndrome, perinatal asphyxia and impaired postnatal cardiopulmonary adaptations (Koskinen et al, 2011;Milla and Zirbes, 2012;Trevino-Alanis et al, 2009;Vela-Huerta et al, 2007). Several studies have reported physiological and structural alterations, mainly restrictive functional abnormalities and fibrosis, that affect the lung of pediatric and adult diabetic patients and of animal models of diabetes (Lawrence et al, 1989;Popov and Simionescu, 1997;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The foundation for curiosity whether lungs are affected by diabetes is based on a few studies: the incidence of asthma in diabetic patients is less than in the residual population, the increased frequency of pulmonary disorders in children born to diabetic mothers and the necessity to understand the pathophysiology of this organ for inhalant anti-diabetic drugs (1,2,3,4,5). A growing mass of data indicates a correlation of diabetes mellitus with lung dysfunction (6,7,8).…”
Section: Introductionmentioning
confidence: 99%